Faulty line detection method based on B‐spline bistable denoising for distribution network. (10th April 2018) - Gao, Jie; Cheng, Qiming; Wang, Xiaowei; Chen, Mingfei
Summary: Neutral‐point ineffectively grounded power system earthed through arc suppression coil is widely used in medium‐voltage distribution system; it is called small current‐to‐ground system (SCGS) in China. When single‐phase‐to‐earth fault occurs at SCGS, the fault current is weak and the noise impairs the feature of fault current, both of which make faulty line detection difficult. Hence, this paper proposes a B‐spline bistable denoising method (BSBD) to process the transient zero‐sequence current. This proposed method consists of 2 approaches: (1) using B‐spline fitting method to improve the deficiency of bistable system and (2) the genetic algorithm used to obtain the parameters of B‐spline bistable system. Then, a faulty line detection criterion (FLDC) based on BSBD and polarity parameter is presented. Electromagnetic transients program is used for testing the BSBD and FLDC. Extensive case studies prove the effectiveness of BSBD and FLDC.